An Exploration of Incorporating Site Response into PSHA Part II: Sensitivity of Hazard Estimates to Site Response Approaches - Papaspiliou,M; Kontoe,S; Bommer,JJ (Soil Dynamics and Earthquake Engineering, 2012)
This paper examines the sensitivity of seismic hazard analyses to various site response analysis procedures. Site effects are incorporated in the hazard calculations using a probabilistic approach and specifically the methodology of Bazzurro and Cornell [1] for the transformation of a generic ground-motion prediction equation to a site-specific one. The paper explores the sensitivity of the median amplification function, its standard deviation and the resulting surface hazard curve, to different methods of site response analysis and model input parameters. The computed site-specific surface hazard curves are also compared with those obtained from a generic soil ground-motion prediction equation. For the two sites investigated, it is shown that the choice of equivalent linear or nonlinear analysis with different constitutive model parameters has a significant impact on the hazard results. The sandy site was seen to be more sensitive to the site response analysis approach employed than the clayey site.